Role of glutamatergic neurotransmission in the enteric nervous system and brain-gut axis in health and disease. (December 2016) - Filpa, Viviana; Moro, Elisabetta; Protasoni, Marina; Crema, Francesca; Frigo, Gianmario; Giaroni, Cristina
Abstract: Several studies have been carried out in the last 30 years in the attempt to clarify the possible role of glutamate as a neurotransmitter/neuromodulator in the gastrointestinal tract. Such effort has provided immunohistochemical, biomolecular and functional data suggesting that the entire glutamatergic neurotransmitter machinery is present in the complex circuitries of the enteric nervous system (ENS), which participates to the local coordination of gastrointestinal functions. Glutamate is also involved in the regulation of the brain-gut axis, a bi-directional connection pathway between the central nervous system (CNS) and the gut. The neurotransmitter contributes to convey information, via afferent fibers, from the gut to the brain, and to send appropriate signals, via efferent fibers, from the brain to control gut secretion and motility. In analogy with the CNS, an increasing number of studies suggest that dysregulation of the enteric glutamatergic neurotransmitter machinery may lead to gastrointestinal dysfunctions. On the whole, this research field has opened the possibility to find new potential targets for development of drugs for the treatment of gastrointestinal diseases. The present review analyzes the more recent literature on enteric glutamatergic neurotransmission both in physiological and pathological conditions, such as gastroesophageal reflux, gastric acid hypersecretory diseases, inflammatory bowel disease, irritable bowel syndrome and intestinal ischemia/reperfusion injury. Highlights: Glutamate is a neurotransmitter in the enteric nervous system and brain-gut axis. Glutamate as an enteric neurotransmitter modulates gut sensory and motor functions. Dysfunction of the enteric glutamatergic transmission is involved in gut diseases.